Estimates of hourly diffuse radiation on tilted surfaces in southeast of brazil - Souza, A. P.; Escobedo, J. F. (My University, 2013)
The global radiation incident on a tilted surfaces consists of components direct, diffuse and reflected from the ground. On a hourly database, the direct radiation can be calculated by geometric projections (ratio of the incidence angle to the solar zenith angle). The reflected radiation has a small effect on calculations and may be calculated with an isotropic model. Both components presents dependence of measures in incidence or horizontal surface. The great difficulty is to evaluate the diffuse radiation by variations of circumsolar, brightness horizontal, isotropic and anisotropic subcomponents. This study evaluated twenty models to estimate hourly diffuse radiation incident on tilted surfaces at 12.85° (latitude - 10°), 22.85° (latitude) and 32.85° (latitude + 10°) facing to North, under different cloudiness sky conditions, in Botucatu, São Paulo State, Brazil (22°53' S, 48°26' W and 786 m above the mean sea level). In contrast, models for estimating the diffuse component show major differences, which justify the validation for local calibrations. There is a decrease of the maximum total radiation scattered with increasing atmospheric transmissivity and inclination angle. The best results are obtained by anisotropic models: Ma and Iqbal, Hay, Reindl et al. and Willmott; isotropic: Badescu and Koronakis, and the Circumsolar model. The increase of the inclination angle allows for a reduction in the performance of statistical parametric models for estimating the hourly diffuse radiation.
Keywords: Atmospheric transmissivity; Indicate statistical; Parametrized models; Solar energy